Durability of natural fiber-reinforced composites of ethylene-propylene copolymer under accelerated weathering and composting conditions - Kumar, A. P.; Depan, Dilip; Singh, R. P. (Journal of Thermoplastic Composite Materials, 2005)
Three types of composites are prepared by the melt mixing of ethylene-propylene copolymer (EPC) with (i) 3 % NaOH-treated jute fiber, (ii) 17.5 % NaOH-treated jute fiber, and (iii) commercial microcrystal line cellulose powder using maleated EPC as compatibilizer. The composites obtained are characterized by FTIR and microscopic measurements. Their mechanical properties are measured using a UTM (Instron model 4204). The durability of the composites is evaluated in an irradiation chamber with UV radiation of wavelength lambda >= 290 mn and composting conditions at different time intervals. The composites made from microcrystalline cellulose show superior mechanical properties, biodisintegrability, as well as photoresistance whereas the specimen containing 3% NaOH-treated fiber exhibited the lowest photoresistance. Increasing the quantity of maleated EP (MEP) in the composition decreases photostability. Neat EPC has been found to be highly stable than all the composites with increasing UV irradiation. It has been found that the composites are less durable under both abiotic and biotic conditions in comparison to the neat polymer.
Keywords: compatibilization; composites; jute fiber; mechanical properties; Microcrystalline cellulose; photodegradation and composting